The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1982-021620145913
|View full text |Cite
|
Sign up to set email alerts
|

Autoavaliação vocal e avaliação perceptivo-auditiva da voz em mulheres com doença tireoidiana

Abstract: Objetivo comparar a autoavaliação vocal e a avaliação perceptivo-auditiva da voz em mulheres com doença tireoidiana. Métodos o estudo foi realizado com 40 pacientes do sexo feminino, idade média de 49,50±10,40 anos, utilizando a escala analógica-visual (EAV) para realizar a autoavaliação vocal e a análise perceptivo-auditiva pelo fonoaudiólogo. A paciente considerou a emissão habitual do dia a dia na sua autoavaliação e para a análise fonoaudiológica da voz foram gravadas amostras da contagem de 1 a 20. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…Some of the most common symptoms in patients after thyroidectomy are roughness, shortness of breath, vocal fatigue and lack of confidence in communication [14]. The voice quality of 350 patients who underwent total thyroidectomy was evaluated by speech therapists, showed that all patients had changes in vocal cord strain and muscular activity of the larynx thereby resulting in a low voice, while patients who did not suffer from such nerve damage showed no changes in voice quality [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most common symptoms in patients after thyroidectomy are roughness, shortness of breath, vocal fatigue and lack of confidence in communication [14]. The voice quality of 350 patients who underwent total thyroidectomy was evaluated by speech therapists, showed that all patients had changes in vocal cord strain and muscular activity of the larynx thereby resulting in a low voice, while patients who did not suffer from such nerve damage showed no changes in voice quality [12].…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that these voice-related symptoms in this particular population have a frequency ranging from 9% to 38%. Symptoms include roughness, shortness of breath, vocal fatigue and lack of confidence in communication [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a self-report visual analogue scale (VAS) is used in several fields to measure the perception of individuals about certain events, such as pain and voice quality (33). The VAS is regarded as reliable and easy to apply (34). Some experts consider this scale for laryngectomized people, but the question involved depends on the type of question it refers to in its application.…”
Section: ' Introductionmentioning
confidence: 99%
“…A voz desempenha um papel fundamental no processo de construção dessa nova identidade, seja na autoaceitação ou na receptividade social (4) e, a autoimagem, mensurada por meio de instrumentos que auxiliam a percepção do sujeito quanto à sua voz, faz parte deste processo (5) . É essencial, portanto, incluir a perspectiva do indivíduo, quando se avaliam os resultados dos procedimentos executados, seja a terapia vocal, cirurgia ou tratamento medicamentoso (6) .…”
Section: Introductionunclassified